2014
DOI: 10.1017/s1049023x14001204
|View full text |Cite
|
Sign up to set email alerts
|

The Use of FAST Scan by Paramedics in Mass-casualty Incidents: A Simulation Study

Abstract: In this simulation study, paramedics had difficulty performing FAST scans with a high degree of accuracy. However, they were more apt to call a patient positive, limiting the likelihood for false-negative triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…Assessment for this study was conducted 6-weeks following initial training and involved a written test with an average score of 82% pre-training versus 71% when performed 12-months later. Regarding the performance of the paramedics, of the seven articles that reported on accuracy measures, sensitivity ranged from 67 to 97.5%, and specificity from 56 to 97% [7, 8, 1719, 23, 25]. The lowest ranges related to a study in mass casualty incidents [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment for this study was conducted 6-weeks following initial training and involved a written test with an average score of 82% pre-training versus 71% when performed 12-months later. Regarding the performance of the paramedics, of the seven articles that reported on accuracy measures, sensitivity ranged from 67 to 97.5%, and specificity from 56 to 97% [7, 8, 1719, 23, 25]. The lowest ranges related to a study in mass casualty incidents [19].…”
Section: Resultsmentioning
confidence: 99%
“…5 ED doctors & 4 paramedics (403 participants total trained from 2003 to 06)US naive. US training day then performed on scene.Evaluate effectiveness of new training course for prehospital FAST (P-FAST)FAST in trauma patientsHealthy models, models with positive FAST (ascites or peritoneal dialysis), and real patientsProspective, multi-centre studyWest et al 2014 USA [19] n  = 9 paramedics (10 enrolled but one pulled out on examination day)Paramedics with field experience but US naïveEvaluate the accuracy andtime taken to perform multiple FAST exams in a simulated MCI setting.FAST in trauma patients during MCIHealthy models and models with positive FAST (peritoneal dialysis patients)Single-blinded RCTVitto et al 2015USA [25] n  = 15 flight nurses and paramedics. US naïveEvaluate the ability of flight nurses and paramedics to learn and retain U/S for use during flight and ground transport.Not ReportedHealthy models and US simulations using US simulatorProspective observational cohort study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 On the other hand, ultrasound has some limitations as well as a very broad range of reported sensitivity and specificity for detecting free fluid and injuries in patients with major trauma. 32 In a MCI simulation study looking for free abdominal fluid detected by Focused assessment with sonography in trauma (FAST, also known as focused abdominal sonography for trauma), the authors observed a false-positive (5overtriage) rate of 59% and a sensitivity of 67%.…”
Section: Ultrasoundmentioning
confidence: 99%
“…32 In a MCI simulation study looking for free abdominal fluid detected by Focused assessment with sonography in trauma (FAST, also known as focused abdominal sonography for trauma), the authors observed a false-positive (5overtriage) rate of 59% and a sensitivity of 67%. 31 The average time needed for a FAST examination was about 2 min.…”
Section: Ultrasoundmentioning
confidence: 99%